Methadone Clients, Crime, and Substance Use - Patterson, Susan (International journal of offender therapy and comparative criminology, 2000)
Self-report criminal activity in a sample of 86 methadone-maintained opioid addicts is examined. Of the participants, 52% report some criminal offending, with drug-related and property crimes accounting for the majority of the offending. One quarter of the females in the sample were involved in prostitution. Of all the demographic factors used in this study, only gender discriminated between the sample in terms of level of offending, with females reporting the highest crime rates. Heroin use and crime measures were also associated, with persistent criminality related to the continued use of heroin. An analysis of the heroin use-criminality association found that only female gender predicted both increased rates of heroin use and increased rates of criminality. Implications of this finding are discussed